Long-Lasting Immune Protection and Other Epidemiological Findings after Chikungunya Emergence in a Cambodian Rural Community, April 2012. - Beatriz Galatas; Sowath Ly; Veasna Duong; Kathy Baisley; Kunthy Nguon; Siam Chan; Rekol Huy; Sovann Ly; Sopheak Sorn; Leakhann Som; Philippe Buchy; Arnaud Tarantola (PLoS Neglected Tropical Diseases)
The East/Central/South African genotype of Chikungunya virus with the E1-A226V mutation emerged in 2011 in Cambodia and spread in 2012. An outbreak of 190 cases was documented in Trapeang Roka, a rural village. We surveyed 425 village residents within 3-4 weeks after the outbreak, and determined the sensitivity and specificity of case definitions and factors associated with infection by CHIKV. Self-reported clinical presentation consisted mostly of fever, rash and arthralgia. The presence of all three clinical signs or symptoms was identified as the most sensitive (67%) and specific (84%) self-reported diagnostic clinical indicator compared to biological confirmation by MAC-ELISA or RT-PCR used as a reference. Having an indoor occupation was associated with lower odds of infection compared with people who remained at home (adjOR 0.32, 95%CI 0.12-0.82). In contrast with findings from outbreaks in other settings, persons aged above 40 years were less at risk of CHIKV infection, likely reflecting immune protection acquired when Chikungunya circulated in Cambodia before the Khmer Rouge regime in 1975. In view of the very particular history of Cambodia, our epidemiological data from Trapeang Roka are the first to support the persistence of CHIKV antibodies over a period of 40 years.